Proactive Modulation in the Spatiotemporal Structure of Muscle Synergies Minimizes Reactive Responses in Perturbed Landings - Munoz-Martel, Victor; Santuz, Alessandro; Bohm, Sebastian; Arampatzis, Adamantios (Frontiers in Bioengineering and Biotechnology, 2021)
Stability training in the presence of perturbations is an effective means of increasing muscle strength, improving reactive balance performance and reducing fall risk. We investigated the effects of perturbations induced by an unstable surface during single-leg landings on the mechanical loading and modular organization of the leg muscles. We hypothesized a modulation of neuromotor control when landing in the unstable condition, resulting in an increase of leg muscle loading. Fourteen healthy adults performed 50 single-leg landings from a 30 cm height onto two ground configurations: stable solid ground (SG) and unstable foam pads (UG). Ground reaction forces, joint kinematics and electromyographic activity of 13 muscles of the landing leg were measured. Resultant joint moments were calculated using inverse dynamics and muscle synergies with their time dependent (motor primitives) and time independent (motor modules) components were extracted via non-negative matrix factorization. Three synergies related to the touchdown, weight acceptance and stabilization phase of landing were found for both SG and UG. When compared to SG, the motor primitive of the touchdown synergy was wider in UG (p < 0.001). Furthermore, in UG the contribution of gluteus medius increased (p = 0.015) and of gastrocnemius lateralis decreased (p < 0.001) in the touchdown synergy. Weight acceptance and stabilization did not show any statistically significant differences between the two landing conditions. The maximum ankle and hip joint moment as well as the rate of ankle, knee and hip joint moment development were significantly lower (p < 0.05) in the UG condition. The spatiotemporal modifications of the touchdown synergy in the UG condition highlight proactive adjustments in the neuromotor control of landings which preserve reactive adjustments during the weight acceptance and stabilization synergies. Furthermore, the performed proactive control in combination with the viscoelastic properties of the soft surface resulted in a reduction of the mechanical loading in the lower leg muscles. We conclude that the use of unstable surfaces does not necessarily challenge reactive motor control, nor increase muscle loading per se. Thus, the characteristics of the unstable surface and the dynamics of the target task must be considered when designing perturbation-based interventions.